O psicótico e o seu ninho: um estudo clínico sobre o setting e os seus destinos - Deus, Ricardo Telles de (2007)
The major goal of this actual study is to distinguish some aspects of the clinical setting that, in the treatment of psychotic patients, would possibly develop an important role. In a first moment, the clinical material collected from the treatment of three psychotic patients attended by the author is built in the form of three narratives. Secondly, many pieces of work that approach the essential subject of this research, in a very meaningful way and under quite singular perspectives, are examined. More specifically, those pieces of work focus on setting in three contexts: in the psychoanalytical clinic, exactly as it would be practiced in the offices; in the institutional sphere; in the Therapeutic Attendance. Lastly, the author of the study got to the conclusion that the clinical setting, adapted to the peculiar needs of the psychotic patient, would present, among many other possibilities, the following characteristics: flexibility or elasticity; consistency; steadiness; materiality; a non-intrusive quality